Inhibition of TNF Receptor p55 By a Domain Antibody Attenuates the Initial Phase of Acid-Induced Lung Injury in Mice - Wilson, Michael R.; Wakabayashi, Kenji; Bertok, Szabolcs; Oakley, Charlotte M.; Patel, Brijesh V.; O’Dea, Kieran P.; Cordy, Joanna C.; Morley, Peter J.; Bayliffe, Andrew I.; Takata, Masao (Frontiers in Immunology, 2017)
Background: Tumor necrosis factor-α (TNF) is strongly implicated in the development of acute respiratory distress syndrome (ARDS), but its potential as a therapeutic target has been hampered by its complex biology. TNF signals through two receptors, p55 and p75, which play differential roles in pulmonary edema formation during ARDS. We have recently shown that inhibition of p55 by a novel domain antibody (dAb™) attenuated ventilator-induced lung injury. In the current study we explored the efficacy of this antibody in mouse models of acid-induced lung injury, to investigate the longer consequences of treatment. Methods: We employed two acid-induced injury models, an acute ventilated model and a resolving spontaneously breathing model. C57BL/6 mice were pretreated intratracheally or intranasally with p55-targeting dAb or non-targeting ‘dummy’ dAb, 1 or 4 hours before acid instillation. Results: Acid instillation in the dummy dAb group caused hypoxemia, increased respiratory system elastance, pulmonary inflammation and edema in both the ventilated and resolving models. Pretreatment with p55-targeting dAb significantly attenuated physiological markers of ARDS in both models. p55-targeting dAb also attenuated pulmonary inflammation in the ventilated model, with signs that altered cytokine production and leukocyte recruitment persisted beyond the very acute phase. Conclusions: These results demonstrate that the p55-targeting dAb attenuates lung injury and edema formation in models of ARDS induced by acid aspiration, with protection from a single dose lasting up to 24 hours. Together with our previous data, the current study lends support towards the clinical targeting of p55 for patients with, or at risk of ARDS.